Trend analysis of medicine consumption based on therapeutic categories in Iran: 2000-2016 - Alireza Yektadoost; Farid Ebrahimi; Mohammadreza Mashouf; Naghmeh Hadidi; Nasser Nassiri Koopaei; Abbas Kebriaeezadeh (Wolters Kluwer Medknow Publications, 2018)
Objective: Iranian healthcare system cost has been remarkably growing during the recent decades. Drug shortages and the economic effects of the sanctions have also exposed the pitfalls and shortcomings of the pharmaceutical system. Moreover, the pharmaceutical system is a major expenditure source for the health system. Pharmaceutical market trend analysis serves as a reliable tool to gather and analyze market and consumption data to take account of the past policies and forecast the future of the market and disease trends. Methods: The present work tries to quantitatively describe and analyze past 17 years of Iranian pharmaceutical market sales data from 2000 to 2016. The anatomical therapeutic chemical-classified drug utilization data obtained from the Iranian Food and Drug Administration were used to analyze the market trends for each therapeutic class and categorize them. Findings: The size of Iranian pharmaceutical market has grown dramatically during the last 5 years reaching to $5.183 billion in 2016 from $3.847 billion in 2011 with a compound annual growth rate of 6.14%. Antidiabetics and antineoplastic agents were one of the most prominent market growth drivers. Introduction of new drug molecules to the market has also contributed to the trend. However, the noncommunicable diseases are gaining momentum in the national disease burden. Conclusion: The market growth necessitates policies to prevent the overwhelming cost burden on the healthcare system which in turn requires well-informed decision-making. Pharmaceutical market trend analysis tries to supply the evidence feed for informed policy-making to forecast, prioritize, and contain the cost burden imposed on the healthcare system by the pharmaceutical sector.